1979
DOI: 10.1084/jem.149.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and pathogenicity of defective Friend spleen focus-forming virus. Decreased transplantability of hemopoietic cells as a marker for preleukemic change.

Abstract: A latent form of persistent infection can be established in susceptible adult mice inoculated with a preparation of defective Friend spleen focus-forming virus (SFFV) purified free from standard leukemia-inducing helper virus (LLV-F). SFFV persistence was initially observed using an in vivo rescue technique in which SFFV could be directly rescued to form splenic foci of malignant erythropoiesis in mice. At approximately 30 d after virus inoculation however, SFFV could not be rescued after inoculation of LLV-F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…We have previously shown SFFVp-induced alterations of hemopoietic stem cell frequency and function (10)(11)(12). Mice reconstituted with serially transplanted stem cells can survive for .8 months free of disease.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…We have previously shown SFFVp-induced alterations of hemopoietic stem cell frequency and function (10)(11)(12). Mice reconstituted with serially transplanted stem cells can survive for .8 months free of disease.…”
mentioning
confidence: 98%
“…Thomsen et al (45) have demonstrated that NK cell activation following lymphocytic choriomeningitis virus infection is associated with the acquired ability of mice to inhibit the growth of syngeneic pluripotent hemopoietic spleen colony-forming stem cells (CFUs). The decreased transplantability of syngeneic CFUs latently infected with replication-defective Friend polycythemia-inducing spleen focus-forming virus (SFFVp) is a hallmark of preleukemic change (10). Multistage Friend disease can be induced by helper-free SFFVp in leukemiasensitive (Fv-2ss) B6.C hosts (C57BL/6-H-7b [47N] congenic with C57BL/6 at Fv-2 [4,10,50]) and is characterized by early effects upon erythroid progenitor cells (30) followed * Corresponding author.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Biological and molecular studies have demonstrated that spleen focus-forming virus (SFFV) is directly responsible for the enhanced proliferation of the erythroid cells in the first step of Friend leukemia (6,9,11). Whether the SFFV genome is also implicated in late malignant erythroid cell transformation has been suggested only by previous studies (4,24). In addition, in this late transformation process an eventual role played by the ecotropic F-MuLV cannot be excluded, even though F-MuLV alone provokes (in certain cases only) late erythroid leukemias after a latency exceeding 3 to 4 months (2, 15).…”
mentioning
confidence: 99%